2021
DOI: 10.3390/pr9091512
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A Effects in Aqueous Environment on Lemna minor

Abstract: The link between different plastic waste pollutants and their impact on the natural aquatic environment and food chain remains a constant and growing issue. Bisphenol A (BPA), a known endocrine disruptor produced in large quantities primarily in the industry of polycarbonate plastics, can accumulate in vegetal and animal tissue, thus magnifying through trophic levels. In this study we exposed viable specimens of the aquatic plant Lemna minor under controlled conditions to 50, 100 and 200 ppm BPA levels in orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…Agricultural evolution has led farming systems to demand inputs that are linked to plastic polymers [18][19][20][21][22]. The characteristics of plastic elements make them one of the primary pollutants in ecosystems, mainly due to their tendency to fragment into small particles, such as microplastics and nanoplastics [23][24][25][26][27][28]; and by the emission, due to ultraviolet radiation from the sun, of some chemical substances that are added during the manufacturing process (additives) to improve the characteristics of the plastic (e.g., biophenol) [29,30]. Unfortunately, the dumping of plastic waste is a common practice and marine ecosystems have experienced the highest incidence of dumping [31,32], which 2 of 19 affects their flora and fauna [25], and its associated microbiome [33]; as well as their physical environment [34].…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural evolution has led farming systems to demand inputs that are linked to plastic polymers [18][19][20][21][22]. The characteristics of plastic elements make them one of the primary pollutants in ecosystems, mainly due to their tendency to fragment into small particles, such as microplastics and nanoplastics [23][24][25][26][27][28]; and by the emission, due to ultraviolet radiation from the sun, of some chemical substances that are added during the manufacturing process (additives) to improve the characteristics of the plastic (e.g., biophenol) [29,30]. Unfortunately, the dumping of plastic waste is a common practice and marine ecosystems have experienced the highest incidence of dumping [31,32], which 2 of 19 affects their flora and fauna [25], and its associated microbiome [33]; as well as their physical environment [34].…”
Section: Introductionmentioning
confidence: 99%
“…Successful examples for photocatalytic phenol degradation, mainly with titanium dioxide (TiO 2 ) as the photocatalyst, are shown in the literature [7][8][9]. Also the plastic additive bisphenol A (BPA), a representative endocrine disruptor and a compound of high concern, belongs to the group of phenolic compounds and can contaminate waters [10]. It is reported that TiO 2 -based photocatalysts are able to degrade BPA, too [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Wastewater can also contain high concentrations of heavy metals, pathogens, pharmaceuticals, plastic additives, and other contaminants. Contaminants can adversely affect plant growth when wastewater is applied to crops [ 7 ]. Human exposure to wastewater contaminants can also be harmful, and agricultural reuse of wastewater has been associated with health risks.…”
Section: Introductionmentioning
confidence: 99%